2018
DOI: 10.3390/coatings8050179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide/ZSM-5 Hybrid on Corrosion Resistance of Waterborne Epoxy Coating

Abstract: Abstract:In this study, the preparation of modified graphene oxide (GO) synergistic structure (ZSM-5-NH-GO) and the effect of this structure on the corrosion performance of epoxy coatings were investigated. The structural and morphological properties of ZSM-5-NH-GO were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The corrosion performances were studied by electrochemical impedance spectroscopy (EIS) and salt spray tests. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…It is clear from the PA-GO figure that more granular materials, small white particles, and more rough folds appear in the single sheet structure. These features are a further indication of phytic acid (PA) grafted on GO [27]. The X-ray photoelectron spectrum analysis curve is shown in Figure 4.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is clear from the PA-GO figure that more granular materials, small white particles, and more rough folds appear in the single sheet structure. These features are a further indication of phytic acid (PA) grafted on GO [27]. The X-ray photoelectron spectrum analysis curve is shown in Figure 4.…”
Section: Resultsmentioning
confidence: 95%
“…We grafted ZSM-5 onto the GO surface to improve the anti-corrosion effect of GO. The results show that this is mainly due to the synergistic effect of the hole/sheet structure to improve the anti-corrosion performance of the coating [27]. However, GO is used in water-based epoxy resins to solve the problems of interlayer forces, water solubility, and dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of strong van der Waals forces and high specific ratio, G, GO or rGO tend to easily aggregate each other, which greatly limits their functional development and industrial applications [5][6][7]. The chemical modification of G, GO or rGO is an efficient method to limit the aggregation, and at the same time, the anticorrosion performance of the nanocomposite coating is enhanced [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of strong van der Waals forces and high specific ratio, G, GO or rGO tend to easily aggregate each other, which greatly limits their functional development and industrial applications [5][6][7]. The chemical modification of G, GO or rGO is an efficient method to limit the aggregation, and at the same time, the anticorrosion performance of the nanocomposite coating is enhanced [8][9][10][11][12][13][14][15][16][17][18][19].GO-PMMA(polymethyl methacrylate) composites were prepared by Chang in the presence of carboxyl compounds, which prevents the agglomeration of graphene in acrylate resin, and the anticorrosion property is twenty-seven times higher than that of pure PMMA film [20]. Polyaniline/4-aminobenzoic acid was also employed by Chang to modify graphene, and the PANI(polyaniline)-G composite with 0.5 wt.% content can reduce the diffusion rate of water and oxygen to 22% and 24% [21].…”
mentioning
confidence: 99%
“…One of the effective methods for improving the corrosion resistance of the waterborne epoxy coating is adding nano pigments, such as mesoporous materials [3][4][5][6][7][8], layered materials [9][10][11], metal-organic frameworks [12,13] and so on. In our previous work, ZSM-5 [14], mesoporous-TiO 2 [15,16], layered double hydroxides and metal-organic frameworks [17] have been investigated as anti-corrosive pigments. The results showed that porous and layered structure can improve the corrosion resistance of coatings via blocking or prolonging the erosion path of corrosive media, which was called the labyrinth effect.…”
Section: Introductionmentioning
confidence: 99%